Constructing 3D and Flexible Plasmonic Structure for High‐Performance SERS Application. Issue 11 (14th August 2018) - Li, Chonghui; Yu, Jing; Xu, Shicai; Jiang, Shouzhen; Xiu, Xianwu; Chen, Chuansong; Liu, Aihua; Wu, Tianfu; Man, Baoyuan; Zhang, Chao
Abstract: Substrate design has attracted much interest in development of an effective surface enhanced Raman scattering (SERS) sensor. A flexible SERS substrate with excellent performance needs to be sensitive to details of the preparation process; this sensitivity represents a significant challenge for practical applications as opposed to laboratory research applications. Here, a 3D flexible plasmonic structure, AgNPs@MoS2 /pyramidal polymer (polymethyl methacrylate), is fabricated using a simple and low‐cost method. Using experiments and theoretical simulations, the SERS performance of the proposed substrate is assessed in terms of its high enhancement factor, ultrasensitivity, quantifiability, reproducibility, stability, and reusability. Finally, the ultralow in situ detection limits of the standard melamine solution and melamine in milk are found to be 10 −10 and 10 −6 m, respectively, which meet the demand for real applications in the food security field. Abstract : 3D flexible plasmonic structure, AgNPs@MoS2 /pyramidal polymer fabricated using a simple and low‐cost method, was demonstrated with high effective surface enhanced Raman scattering (SERS) performance from experiment and theory. The in‐situ detection limits of the standard melamine solution and melamine in milk are 10 −10 and 10 −6 m, respectively, which meet the demand for real food security field applications.